Lentinula edodes Polysaccharides Inhibit Estrogen Biosynthesis Enzymes in Hormone-Dependent Breast Cancer - Ponnusamy, Chandrasekaran; Uddandrao, V V Sathibabu; Sasikumar, Vadivukkarasi; Prabhu, Puniethaa; Ganapathy, Saravanan (Indian Journal of Pharmaceutical Education and Research, 2026)
Background / Objective: Breast cancer, a leading cause of death among women, is closely associated with estrogen metabolism. This study investigated the potential of partially purified polysaccharides from Lentinula edodes (shiitake mushroom) as natural inhibitors of key enzymes involved in estrogen production aromatase, estrone sulfatase, and 17β hydroxysteroid dehydrogenase which are vital in the progression of hormone-dependent breast cancer. Materials and Methods: Polysaccharide fractions were purified using ion-exchange and size-exclusion chromatography. Enzyme inhibition was assessed through ELISA and colorimetric assays, which revealed concentration-dependent inhibition, with the highest activity observed at 400 µg/mL: aromatase (87.25%, IC₅₀=181.25 µg/mL), estrone sulfatase (86.62%, IC₅₀=187.5 µg/mL), and 17β hydroxysteroid dehydrogenase (86.67%, IC₅₀=208.4 µg/mL). GC-MS analysis identified 33 bioactive compounds, of which 14 were evaluated for pharmacokinetic and drug-likeness properties using SwissADME. Results: Molecular docking showed strong binding interactions between selected compounds (D-fructose and diethyl mercaptal pentaacetate) and the target enzymes, supporting their inhibitory potential. In silico toxicity predictions further confirmed favorable safety profiles. Conclusion: Collectively, these findings highlight L. edodes-derived polysaccharides and associated bioactive molecules as promising natural inhibitors of estrogen biosynthesis, offering new perspectives for therapeutic strategies against hormone-dependent breast cancer.
Keywords: Lentinula edodes; Breast Cancer; Natural products; Estrogen biosynthesis Enzymes